Image of Natesha on the central bhadra - Temples of India Project Team (Jio Institute, 2024)
The central bhadra of the east-facing jangha of the temple has a Natesha icon. The devakoshtha that frames the Natesha is similar in style to the devakoshtha on the east-facing jangha. The eight-handed Natesha is in a dancing posture holding a snake, kapala, khatvanga, trishula, and damaru attributes. Natesha has a jata mukuta (matted hair) and a halo behind his head. There are two dancing figures that are likely attendants at the feet of Natesha.